Development of Multiphase Diffraction Pattern Analysis Technique with Rietveld Refinement Method: PZT Thin Case Study - Rizky Arief Shobirin; Masruroh Masruroh; Rachmat Triandi Tjahjanto (Natural B, Journal of Health and Environmental Sciences, 2017)
In this research has been developed multifasa diffraction pattern analysis technique with rietveld refinement method with case study of application of the technique on thin layer of PZT (PbZrxTi (1-x) O3) which has been synthesized with variation of 1, 2, and 3 hour annealing time. This interpretation technique begins with the determination of the background, then performed refinement parameter determinant of pattern change, peak shape, and intensity of diffraction. The parameters are, respectively, scaling factor, 2θzero, lattice parameter, gaussian peak shape constant, and gaussian-lorentzian, atomic position coordinates, and preferred orientation. The refinement results show that changes in peak shape constant give significant changes in residual values, whereas atomic and preferred orientation changes do not provide significant change in residual values.